2020
DOI: 10.1002/anie.202000579
|View full text |Cite
|
Sign up to set email alerts
|

Primary Anion–π Catalysis of Epoxide‐Opening Ether Cyclization into Rings of Different Sizes: Access to New Reactivity

Abstract: The concept of anion–π catalysis focuses on the stabilization of anionic transition states on aromatic π surfaces. Recently, we demonstrated the occurrence of epoxide‐opening ether cyclizations on aromatic π surfaces. Although the reaction proceeded through unconventional mechanisms, the obtained products are the same as those from conventional Brønsted acid catalysis, and in agreement with the Baldwin selectivity rules. Different mechanisms, however, should ultimately lead to new products, a promise anion–π c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 65 publications
(26 reference statements)
1
33
0
Order By: Relevance
“…On the other hand, experimental studies have revealed that Michael-addition between malonic acid half thioester (37) and enolate acceptor 38 fails without anion-π catalyst and hence leads to solely the formation of a decarboxylation product 40. Fortunately, the presence of anion-π catalyst for the same reaction leads to the formation of an addition product (39) selectively in comparison to decarboxylation product (40) (Figure 5). [16] Besides these significant catalytic studies of anion-π interactions, the anion-π catalytic domain has now been explored to iminium, [18] enamine, [15] oxocarbenium, and transamination chemistry.…”
Section: Schematic Illustration Of Kemp Elimination Reaction Along Wimentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, experimental studies have revealed that Michael-addition between malonic acid half thioester (37) and enolate acceptor 38 fails without anion-π catalyst and hence leads to solely the formation of a decarboxylation product 40. Fortunately, the presence of anion-π catalyst for the same reaction leads to the formation of an addition product (39) selectively in comparison to decarboxylation product (40) (Figure 5). [16] Besides these significant catalytic studies of anion-π interactions, the anion-π catalytic domain has now been explored to iminium, [18] enamine, [15] oxocarbenium, and transamination chemistry.…”
Section: Schematic Illustration Of Kemp Elimination Reaction Along Wimentioning
confidence: 99%
“…On the π-acidic surface of 13, they have carried out asymmetric addition of 54 to nitroolefin enamine acceptor 55. The NDI π-acidic surface helps in the stabilization of transition state of anion near nitronate intermediate by anion-π interactions as can be observed from the structures of Schematic depiction of addition product (39) selectivity over decarboxylated product (40) by means π-stacked foldamer assisted anion-(π) n -π catalysis.…”
Section: Schematic Illustration Of Kemp Elimination Reaction Along Wimentioning
confidence: 99%
See 1 more Smart Citation
“…This inversion of the head‐to‐tail directionality with 1,5 trans ‐diepoxide 3 to the tail‐to‐head directionality with 1,4 trans ‐diepoxide 11 was as designed. Namely, shortening of the tether of the alcohol nucleophile from three carbons in 4‐epoxyalcohol 3 to two carbons in 3‐epoxyalcohol 11 should disfavor head‐to‐tail cyclization into the smaller, more strained rings [18] . Instead, the central epoxide oxygen opens the pnictogen‐bonding activated terminal epoxide.…”
Section: Figurementioning
confidence: 99%
“…Namely, shortening of the tether of the alcohol nucleophile from three carbonsi n4 -epoxyalcohol 3 to two carbons in 3-epoxyalcohol 11 should disfavor head-to-tail cyclization into the smaller, more strained rings. [18] Instead, the central epoxide oxygen opens the pnictogen-bonding activated terminal epoxide. This tail-to-head cyclization occurs with anti-Baldwin endo-tet selectivity because the Baldwin isomer would be highly strained.…”
mentioning
confidence: 99%